Fine exploration and green development of ion-adsorption type REE deposits in South China using multi-geophysical technology - Tao, Jian-Li; Deng, Yi-Chao; Ye, Dong-Xu; Chen, Bin-Feng; Zhou, Yao; Zhong, Jian-Guo; Wang, Xu; Wang, Wei (Frontiers in Earth Science, 2025)
For a long time, the exploitation of ion-adsorption type rare earth (REE) deposits in the southern Jiangxi Province of China have been accompanied by ecological and environmental damage, making the search for green and efficient mining solutions particularly important. Currently, in-situ leaching is the main mining technique used for ion-adsorption REE deposits. Before employing this technique, it is imperative to thoroughly investigate the geological mining conditions. Environmental damage caused by the failure to do so, low recovery rates of the original liquor, and secondary geological disasters pose serious challenges to green and efficient mining operations. In this work, microtremor surveying technology was introduced in the Kaizidong mining area in southern Jiangxi Province to refine exploration of the subsurface stratigraphy. By utilizing the wave velocity discontinuity interfaces at 350 m/s and 500 m/s, the layers of the rare earth mine is accurately delineated, including the completely weathered layer, the semi-weathered layer, and the bedrock, providing a critical basis for in-situ leaching mining. Subsequently, high-density resistivity method was employed to monitor and measure the flow direction of the original liquor. After the apparent resistivity of the two observational profiles stabilized, they decreased by 57.77% and 63.25%, respectively. Using the variations in resistivity to infer the distribution of the original liquor and simulate its flow direction, the injection and recovery system was adjusted in a timely manner to eliminate potential safety hazards during mining. The exploration of a combined geophysical method of microtremor detection and high-density electrical method has enabled the establishment of a geological model for the entire mine’s subsurface structure, guiding the in-situ leaching mining process of ion-adsorption REE mines towards an economic, efficient, and green development.